(untitled) (MAUSAM, 2005)
During December 2002 – early April 2003, between 2345 and 0215 UTC and between 1230 and 1400 UTC covering the twilight period, radar reflectivities as high as 28-38 dBZ were measured in the atmospheric boundary layer by the Doppler Weather Radar (DWR) installed at Cyclone Detection Radar station, Chennai regularly. On analysis, it was found that these radar returns were not from precipitating clouds but from some other invisible source(s). The contributory mechanisms for this high order of reflectivity have been analysed from meteorological and non-meteorological angles. Thermodynamical parameters and potential radio refractive index have been computed and analysed. The refractive index structure constant (Cn2) has been computed from the 0000 and 1200 UTC RS/RW data as well as from the radar reflectivity data. The prevalence of convectively unstable atmosphere in the first layer adjacent to the surface (upto 350 m a.g.l) at 1200 UTC and nocturnal surface inversion at 0000 UTC contribute to the enhanced Cn2 in the range of 3.58 ´ 10-12 to 10-15 m-2/3 in the layers upto 900 m a.g.l. This sort of Bragg scattering with high Cn2 could have contributed to radar reflectivity factor as high as +0.8 dBZ only. During the last three decades, there is an alarming increase in nocturnal surface inversion frequencies over Chennai presumably due to high concentration of suspended particulate matters and respirable dust particles. The contribution by these pollutants to the radar reflectivity factor is restricted to a maximum of about – 0.9 dBZ only. Migratory birds of about eight to twelve thousand in number with 10 – 50 cm2 radar cross section and possibly innumerable insects appear as sources of the enhanced reflectivity.